Graphene enriched with pyrrolic coordination of the doped nitrogen as an efficient metal-free electrocatalyst for oxygen reduction - Unni, SreeKuttan M.; Devulapally, Saikrishna; Karjule, Neeta; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
We report an efficient template-free synthetic route for the preparation of mesoporous nitrogen-doped graphene (NGE) containing a high weight percentage of pyrrolic nitrogen, good specific surface area and comparable electrochemical oxygen reduction activity as that of the state-of-the-art 40 wt% Pt/C catalyst. The desired coordination of nitrogen in the carbon framework of graphene has been conceived by a mutually assisted redox reaction between graphene oxide (GO) and pyrrole, followed by thermal treatment at elevated temperatures. NGE exhibits a high surface area of 528 m(2) g(-1) and a pore diameter of similar to 3 to 7 nm. The heat treatment temperature plays a pivotal role in establishing the desired pyrrolic coordination of nitrogen in graphene for the electrochemical oxygen reduction reaction. The NGE sample obtained after heat treatment at 1000 degrees C (NGE-1000) has 53% pyrrolic nitrogen content compared to the similar samples prepared by treating at low temperatures. Most importantly, NGE-1000 has displayed a significantly low overpotential for oxygen reduction with the onset potential very closely matching that of the commercial 40 wt% Pt/C. It is noteworthy that the reaction involves the desired 4 electron transfer as observed in the case of the Pt based electrocatalysts, leading to a significantly high kinetic current density of 6 mA cm(-2) at -0.2 V. Moreover, the fuel tolerance and durability under the electrochemical environment of the NGE catalyst is found to be superior to the Pt/C catalyst.